Representações sociais de suicídio nas mídias digitais : um estudo sobre os efeitos Werther, Papageno e Severino - Lucas, Lorena Schettino (2024)
Challenging professionals from different areas of knowledge in the construction of explanatory theories and in the application of effective prevention strategies, suicide emerges as a phenomenon that mobilizes affections and positions taken by individuals and social groups. In the historical production on the topic, it is observed that it assumes different functions in the dynamics of societies over the centuries, configuring itself as an issue that requires interventions at various levels of care, including in media coverage. This Thesis, guided by the theoretical-methodological and conceptual framework of the Social Representations Theory (SRT), aimed to analyze the social representations of suicide in reports on suicide published on the social network Twitter by the newspaper Folha de São Paulo, between 2015 and 2021, and in the comments made by internet users in these online reports. To this end, three complementary documentary studies were carried out, namely: i) analysis of the effects of contagion and prevention in reports on suicide published on Twitter by the newspaper Folha de São Paulo in accordance with international criteria for suicide prevention by the media; ii) analysis of social representations of suicide, the individual who commits suicide and the context in which suicide occurs in reports on suicide published by the newspaper Folha de São Paulo on Twitter; and iii) investigation of the shared field, the organizing principles of position taking and the psychosocial anchoring of Twitter users in relation to social representations of suicide. The data were analyzed through the evaluation of reports using an instrument created for this study, Content Analysis, Pearson's chi-square and Fisher's exact tests, simple Poisson and simple multinomial regressions, descriptive statistical analyzes, Factorial Correspondence Analysis and Descending Hierarchical Classification. In an integrated way, the results demonstrated that 39.81% of the analyzed reports contribute to the suicide contagion effect, 23.30% contribute to the prevention effect and 31.07% contribute to both. Regarding the content of the reports, oppositional and complementary relationships were observed regarding the object of suicide, descriptive, pejorative and romanticized names about those who commit suicide and descriptions of the social and individual contexts associated with the phenomenon. In relation to the organization of the representational field, the presence of three organizing principles of the meanings linked to suicide by Twitter users were noted: science, religion and politics. The communicative modalities of social representations are discussed, namely, diffusion, propagation and propaganda, and the application of such concepts in the cybernetic reality of the contemporary era. Points that refer to the psychosocial triad and the media entity as a subject of representation and agent of psychosocial changes are also addressed, in addition to reflections on the dual narratives about suicide that make up the media game. Finally, we discuss the effect that social representations of suicide conveyed by the media can have on social reality, which is called the Severino Effect, and discuss the possibilities of psychosocial intervention based on this concept. This Thesis also contributed to the creation of an instrument for analyzing media materials for suicide prevention, to the innovation regarding the use of the SRT societal approach in a documentary study and to the proposition of studying suicide based on the framework theoretical-methodological approach to SRT, followed by the possibilities of intervention considering the Severino Effect